Bony fixation in the era of spinal robotics: A systematic review and meta-analysis. (March 2022) - Himstead, Alexander S.; Shahrestani, Shane; Brown, Nolan J.; Produturi, Gautam; Shlobin, Nathan A.; Al Jammal, Omar; Choi, Elliot H.; Ransom, Seth C.; Daniel Diaz-Aguilar, Luis; Sahyouni, Ronald; Abraham, Mickey; Pham, Martin H.
Highlights: Limited literature exists on robotic placement of non-pedicle screw trajectories. Nine screw trajectories were identified in the literature. S2-alar-iliac, sacroiliac, and cortical bone trajectory were most common. Robotic screw placement was more accurate than conventional. Eight robotic platforms were identified with accuracy rates greater than 93% Abstract: Background: Accurate spinal screw placement in spinal instrumentation is of utmost importance to avoid injury to surrounding neurovascular structures. This study was performed to investigate differences in accuracy, operating room time, length of stay, and operative blood loss across studies involving all types of spinal fixation. Methods: PubMed, EMBASE, and Scopus were systematically queried to identify articles that fit the inclusion and exclusion criteria. Meta-analysis was performed using R software, and odds ratios and 95% CIs were calculated. Results: Sixty-nine articles were included in qualitative synthesis, and 35 studies in the meta-analysis, for a total of 8, 174 robotically placed screws in 1, 492 patients compared to 9, 791 conventionally placed screws in 1, 638 patients. A total of 9 screw trajectories were studied in the literature, although only 4 had enough evidence to be included in the meta-analysis. Robotic screw placement was more accurate than conventional screw placement (OR 2.24; 95% CI, 1.71–2.94). Robotic placement was not associated with significantly different postoperative length of stay (SMD −0.32; 95% CI, −1.20, 0.51), operative blood loss (SMD −0.25; 95% CI, −0.79, 0.19), or operative duration (SMD 0.08; 95% CI −1.00, 1.39). A total of 8 robotic platforms were found in the literature with accuracy rates above 93%. Conclusion: Robotic spinal fixation is associated with increased screw placement accuracy and similar operative blood loss, length of stay, and operative duration. These findings support the safety and cost-effectiveness of robotic spinal surgery across the spectrum of robotic systems and screw types.